1995
DOI: 10.1177/00220345950740010801
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin at Micromolar Concentrations is an Osteogenic Agent for Human-mandible-derived Bone Cells in vitro

Abstract: The present study sought to test the hypothesis that phenytoin acts on normal human-mandible-derived bone cells to induce osteogenic effects. To test the effects of phenytoin on bone cell proliferation, we measured [3H]-thymidine incorporation into cell DNA during the final four hr of a 24-hour incubation with phenytoin. Phenytoin at micromolar concentrations significantly stimulated the [3H]-thymidine incorporation in a dose-dependent, biphasic, manner with a maximal effect at from 10 to 50 microM. We confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…6,7 In vivo and in vitro studies have demonstrated that phenytoin increases osteoblast number, osteoid thickness, surface, and volume of rat bone tissues 8,9 and that it increases markers of osteogenesis for humans. 10,11 These findings indicate that phenytoin is an osteogenic agent.…”
Section: Abstract Phenytoin/adverse Effects; Torus/palatal; Torus/mamentioning
confidence: 86%
“…6,7 In vivo and in vitro studies have demonstrated that phenytoin increases osteoblast number, osteoid thickness, surface, and volume of rat bone tissues 8,9 and that it increases markers of osteogenesis for humans. 10,11 These findings indicate that phenytoin is an osteogenic agent.…”
Section: Abstract Phenytoin/adverse Effects; Torus/palatal; Torus/mamentioning
confidence: 86%
“…However, the racial composition of the phenytoin group was diverse and no racial group predominated. Phenytoin has also been reported to have direct effects on bone resorption [20][21][22] and formation, 23,24 may directly impair calcium absorption, 24 and may impair the response of osteoblasts to PTH. 22,25 Although carbamazepine has also been shown to inhibit bone formation 23 and intestinal calcium absorption, 24 it is possible that the bone loss we observed may be mediated by one or more direct effects of phenytoin on some aspect of bone and mineral metabolism that are not shared by carbamazepine, rather than by an indirect effect of phenytoin on vitamin D metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, the racial composition of the phenytoin group was diverse and no racial group predominated. Phenytoin has also been reported to have direct effects on bone resorption [20][21][22] This study also has several important limitations. We did not include a group of women without epilepsy to serve as normal controls.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 92%
“…Whereas, the relative contribution of individual VGSCs to modulate monocyte/macrophage remains to be elucidated. It has been demonstrated that PHT treatment is associated with enhanced local production of vascular-endothelial growth factor (VEGF) [47], acidic fibroblast growth factor [48], platelet-derived growth factor [49] and TGF-β1 [50], which are all essential for neovascularization. Moreover, compared with Ly6C+ subset, Ly6C- monocytes selectively expressed higher levels of VEGF [43].…”
Section: Discussionmentioning
confidence: 99%